In Pursuit of Liberalism International Institutions in Postcommunist Europe - Epstein, Rachel A. (Johns Hopkins University Press, 2008)
Though the fall of the Soviet Union opened the way for states in central and eastern Europe to join the world of market-oriented Western democracies, the expected transitions have not been as easy, common, or smooth as sometimes perceived. Rachel A. Epstein investigates how liberal ideas and practices are embedded in transitioning societies and finds that success or failure depends largely on creating a social context in which incentives held out by international institutions are viewed as symbols of an emerging Western identity in the affected country.Epstein first explains how a liberal worldview and institutions like the European Union, World Bank, the International Monetary Fund, and the North Atlantic Treaty Organization go hand-in-hand and why Western nations assume that a broad and incremental program of incentives to join will encourage formerly authoritarian states to reform their political and economic systems. Using Hungary, Poland, Romania, and the Ukraine as case studies, she demonstrates the limits of conditionality in the face of national social perceptions and elucidates the three key points around which a consensus within the state must emerge before international institutions can expect liberalization: domestic officials must be uncertain about how changing policies will affect their interests; the status of international and domestic institutions must not be in jeopardy; and the proposed polices must seem credible. In making her case, Epstein cleverly bridges the gap between the rationalist and constructivist schools of thought.Offering new data on and fresh interpretations of reforming central bank policies, privatizing banks with foreign capital, democratizing civil-military relations, and denationalizing defense policy, In Pursuit of Liberalism extends well beyond the scope of previous book-length studies.